2010
DOI: 10.1186/1743-422x-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Species and age related differences in the type and distribution of influenza virus receptors in different tissues of chickens, ducks and turkeys

Abstract: We undertook one of the most detailed studies on the distribution of α2,3 sialic acid (SA)-galactose (gal) (avian type) and α2,6SA-gal (human type) receptors on different tissues of chickens, ducks and turkeys of varying age groups. On the tracheal epithelium, all 3 bird species expressed strong positive staining (80-90%) for α2,3SA-gal receptors in the 3 different age groups. In addition, a lesser amount of α2,6SA-gal receptors (30-90%) were observed with slight differences in distribution with age and specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 37 publications
7
65
2
1
Order By: Relevance
“…These types of linkages are frequent in human respiratory epithelia (36). In contrast, the HA of avian strains bind preferentially to ␣2,3-linked sialic acids (SA␣2,3), which are abundant in the avian intestinal tract (33).…”
mentioning
confidence: 99%
“…These types of linkages are frequent in human respiratory epithelia (36). In contrast, the HA of avian strains bind preferentially to ␣2,3-linked sialic acids (SA␣2,3), which are abundant in the avian intestinal tract (33).…”
mentioning
confidence: 99%
“…Terminal sialic acid linkage to the penultimate sugar of the glycan chain occurs via carbon 3 or carbon 6, giving the two isomers ␣-2,3 and ␣-2,6 SA, respectively (32). The human upper respiratory tract, the primary site of influenza virus replication in the human host, has abundant SA of the ␣-2,6 isomer, while in the avian gut, the site of replication in avian hosts, the ␣-2,3 conformer predominates, as demonstrated by isoform-specific lectin staining (22,23,38). Among a variety of factors that influence tropism, a major host adaptation facilitating avian influenza virus infection and transmission among humans is mutation in the receptor binding pocket of the HA protein to allow efficient ␣-2,6 SA rather than ␣-2,3 SA binding (19,21,33).…”
mentioning
confidence: 99%
“…In particular, these Eurasian poultry influenza viruses displayed good binding to ␣2-6-linked sialic acids (37,53). Studies on expression of sialic acids in intestinal and respiratory epithelia of different birds revealed substantial host-specific distinctions, among them, expression of both Neu5Ac␣2-3Gal-and Neu5Ac␣2-6Gal-terminated sialyloligosaccharides in chicken and quail, in contrast to ducks, which mainly contain Neu5Ac␣2-3Gal in their intestinal epithelium (16,19,23,29,49,63). Taken together, these findings indicated that influenza viruses perpetuated in different birds can have different receptor specificities owing to distinctions in the sialic acid receptors in these avian species.…”
mentioning
confidence: 99%